2018
DOI: 10.1364/josaa.35.000b85
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual resolution of color for multiple chromatically ambiguous objects

Abstract: In a classic study, Kovács et al. [Proc. Natl. Acad. Sci. USA 93, 15508 (1996)] used an array of many disks presented dichoptically with half of the disks in one eye “red” and the other half “green;” disk chromaticities in the fellow eye were reversed, resulting in binocular color rivalry for every disk, thus creating color ambiguity. Surprisingly, the binocularly fused percept sometimes was all disks of the same color (red or green), which showed that perceptual resolution of the many ambiguous neural represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Previous work has shown that multiple chromatically rivalrous discs viewed simultaneously and presented with ISR all appear the same color far more often than chance (Slezak & Shevell, 2018). This implies grouping among the discs; that is, the color of each rivalrous disc in view is not determined independently of the others.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous work has shown that multiple chromatically rivalrous discs viewed simultaneously and presented with ISR all appear the same color far more often than chance (Slezak & Shevell, 2018). This implies grouping among the discs; that is, the color of each rivalrous disc in view is not determined independently of the others.…”
Section: Resultsmentioning
confidence: 97%
“…In ISR, luminance-defined form also has been found to produce percepts consistent with dominance of monocularly driven neural representations (Lee & Blake, 1999; Denison & Silver, 2012; Brascamp, Sohn, Lee, & Blake, 2013). Equiluminant chromatic stimuli presented in ISR, however, give percepts accounted for by competition between binocularly driven neurons and minimize or eliminate the monocular dominance found with SBR (Slezak & Shevell, 2018). The current study did not find evidence for monocular cues influencing grouping during chromatic ISR, as there never was a significant difference between conventional and patchwork rivalrous stimuli (Experiment 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations